Using technology to accomplish comparability of provision in distributed medical education in Canada: an actor–network theory ethnography. Issue 11 (2nd November 2018) - Tummons, Jonathan; Fournier, Cathy; Kits, Olga; MacLeod, Anna
ABSTRACT: This article is derived from a three-year ethnography of distributed medical education at one Canadian University across two Canadian provinces. It explores the ways in which students and staff work inside the technologically rich teaching environments within which the curriculum is delivered. Drawing on data constructed through observations, interviews and photographs, the article seeks to explain how the key concept of comparability of provision is accomplished. The article concludes that the education received at both campuses is comparable. However, simply to attribute this comparability to the technology itself is to ignore the central role that is played by the staff – academic, administrative and audio-visual. The article concludes by arguing that, notwithstanding the fact that people will always respond to technologies in unanticipated ways, the curriculum within which they are enfolded is sufficiently robust to accommodate such practices whilst at the same time maintaining the quality of the provision.